2018
DOI: 10.7150/ijms.27669
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Vitamin D Orchestrate Adipose Derived Stem Cell Fate by Modulating Epigenetic Regulatory Genes

Abstract: Melatonin, that regulates many physiological processes including circadian rhythms, is a molecule able to promote osteoblasts maturation in vitro and to prevent bone loss in vivo, while regulating also adipocytes metabolism. In this regard, we have previously shown that melatonin in combination with vitamin D, is able to counteract the appearance of an adipogenic phenotype in adipose derived stem cells (ADSCs), cultured in an adipogenic favoring condition. In the present study, we aimed at evaluating the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Understanding the molecular mechanisms involved in these alterations could contribute in controlling adipogenesis and its related metabolic complications, as cardiovascular risk. Within this context, we previously demonstrated that the combination of melatonin and vitamin D is able to counteract adipogenic differentiation in ADSCs, reducing cytoplasmatic fatty acid accumulation and maintaining the pluripotency of stem cells [ 33 , 34 ]. In the present paper, we evaluated the effect of metformin and vitamin D, alone or in combination, on ADSC adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular mechanisms involved in these alterations could contribute in controlling adipogenesis and its related metabolic complications, as cardiovascular risk. Within this context, we previously demonstrated that the combination of melatonin and vitamin D is able to counteract adipogenic differentiation in ADSCs, reducing cytoplasmatic fatty acid accumulation and maintaining the pluripotency of stem cells [ 33 , 34 ]. In the present paper, we evaluated the effect of metformin and vitamin D, alone or in combination, on ADSC adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of thyroid hormone on lipid metabolism is complex and poorly understood. Lipid metabolism is regulated by different enzymes, which are regulated by different specific gene and hormones [20,21] and lack of thyroid hormone causes elevation in total cholesterol and LDLc by changes in the synthesis, metabolism, and mobilisation of lipids [22].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is important in a wide range of physiological processes, and its deficit has been related to different chronic diseases and metabolic conditions, including obesity. Nonetheless, encompassing literature studies indicated only a faint association between gene variants acting in vitamin D metabolism and the obese phenotype [33], while the environment seems to play a major role [34][35][36]. The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to the six susceptibility loci harboring genome-wide significant SNPs (recently identified in a large GWAS) is 7.5%, with statistically significant loci explaining 38% of this total [37].…”
Section: Discussionmentioning
confidence: 99%